Cyanoacrylate glue in breast surgery: the GLUBREAST Trial - Esposito, Emanuela; Siani, Claudio; Donzelli, Ivana; Crispo, Anna; Coluccia, Sergio; Di Gennaro, Piergiacomo; Luongo, Assunta; Avino, Franca; Fucito, Alfredo; Marone, Ugo; Melucci, Maria Teresa; Saponara, Ruggero; et al. (Frontiers in Oncology, 2025)
IntroductionIn 2018, the National Cancer Institute of Naples has launched the GLUBREAST Trial to verify the efficacy of cyanoacrylate sealing glue to prevent or reduce seroma after axillary dissection in breast surgery. The glue is a synthetic sealant (N-Butyl-2-CyanoAcrylate+Metacryloxisulfolane) biocompatible, CE approved for internal human uses and surgical procedures. The assumed mechanism of action in breast surgery is that the glue would create a seal coating in the operative field to occlude lymphatic leaks and limit seroma formation.Materials and methodsThe trial included 180 patients scheduled for breast-conserving surgery or for radical modified mastectomy without reconstruction. Out of 180 patients, 91 were randomized to receive suction drain and sealant glue after axillary dissection (Experimental Arm), whereas 89 patients (Control Arm) received suction drain without glue.StatisticsA multivariable mixed effect model on presence of liquid drained and volume drained was calculated. Stratified models by visits were performed.ResultsThe trial ended in June 2022. Older age was associated with a higher volume of seroma drained per day (β 0.30; 95% CI: 0.00–0.60). A 5-U increase in body mass index was associated with higher daily drained seroma volume in patients who underwent breast-conserving surgery (β 5.0; 95% CI: 0.62–9.4), but not in patients who underwent mastectomy (β 2.5; 95% CI: −3.6–8.6). We did not find statistically significant differences in presence of liquid drained and volume drained among the study groups. An advantage for the Experimental Arm was observed from third and fourth to fifth outpatient visits without reaching a statistical significance (p=0.069 and p=0.072, respectively); so far, 5% of patients in the Experimental Group had clinical benefit from the glue.ConclusionsThe vast majority of data in the literature come from case series, and surgeons need a higher level of evidence to drive surgical decision-making and choose proper devices to increase patient quality of life. The GLUBREAST randomized trial tested the efficacy of cyanoacrylate sealing glue to prevent postoperative seroma in breast surgery. Although only a small number of patients benefited from sealant application, we regret to say this trial has some limitation, i.e., the prolonged presence of suction drain. Further research is warranted to better clarify the benefit of cyanoacrylate glue in breast surgery.